6(9y-8)=46+7y

Simple and best practice solution for 6(9y-8)=46+7y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(9y-8)=46+7y equation:


Simplifying
6(9y + -8) = 46 + 7y

Reorder the terms:
6(-8 + 9y) = 46 + 7y
(-8 * 6 + 9y * 6) = 46 + 7y
(-48 + 54y) = 46 + 7y

Solving
-48 + 54y = 46 + 7y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-7y' to each side of the equation.
-48 + 54y + -7y = 46 + 7y + -7y

Combine like terms: 54y + -7y = 47y
-48 + 47y = 46 + 7y + -7y

Combine like terms: 7y + -7y = 0
-48 + 47y = 46 + 0
-48 + 47y = 46

Add '48' to each side of the equation.
-48 + 48 + 47y = 46 + 48

Combine like terms: -48 + 48 = 0
0 + 47y = 46 + 48
47y = 46 + 48

Combine like terms: 46 + 48 = 94
47y = 94

Divide each side by '47'.
y = 2

Simplifying
y = 2

See similar equations:

| 112x^2-56x+21= | | -6x-26=7(7-3x) | | 4(v+9)-5v=43-v | | 2+2=d | | -8(-3x-9)-8=10x-20 | | 0.7x+12.8=x-1.93 | | r^2-5r+1=0 | | 2(2x-3.8)=8x-7.6 | | 10(2p+5)=-15+7p | | -0.6x+3.97=-0.8x+2.37 | | -5(x-4)+10=45-10x | | 6.6+0.9x=0.3 | | -2w-9(6-10w)=29+5w | | 10x-10=5x-2 | | 7x^4-13x^2-15= | | 6+2(9+4x)=5x+3 | | x^3-4x^2-11x=-30 | | BD=2(a+1) | | 3+4ab-9b^2= | | 3(x+2.64)=2x | | AC=2(5a+1) | | 600x-0.34=100x+0.81 | | -2x+10=10y | | 1.1x+2-4.1x=8 | | X+2/2=10-x+2/3 | | -3x+y=-17 | | 5x-32.4=x | | 0.4x+0.9=-1.1 | | 18-7x=2x | | 2/9r+10=-10 | | 6(2-t)-(4-4t)=5 | | 4(3-t)-(2-2t)=7 |

Equations solver categories